Leaf application of nitrogen in different phenological stages in soybean and inoculation with Bradyrhizobium japonicum - Buratto, Willian; Buratto, Weslley; Oliveira, Amanda Martins de; Oliveira, Reginaldo de [UNESP]; Caione, Gustavo; Seben Junior, Getulio de Freitas (Univ Federal Mato Grosso, 2018)
Nitrogen fertilization in soybean crop, associated with inoculation with a bacterium Bradyrhizobium japonicum is a common practice in agriculture, however, much contested. The objective of this study was to evaluate the response of soybeans to foliar application of N in different stages of phenology and the application of inoculant with the diazotrophic bacterium Bradyrhizobium japonicum. The experiment was carried out in a greenhouse at the State University of Mato Grosso, Alta Floresta-MT. The completely randomized experimental design was used in a 4x2 factorial arrangement, with 4 nitrogen application times (R1 - Beginning of flowering, R3 - Final flowering, R5.1 - Grains perceptible to touch and R5.3 - Most pods between 25 -50% granulation) and presence or absence of Bradyrhizobium japonicum, with 4 replicates. It was concluded that the application of leaf nitrogen in the non-stage soybean crop provided an increase in the accumulation of nitrogen in the aerial part, there is no number of pods and grains per plant. The presence of the inoculant provided a larger number of pods when applicable. N in the periods R1 and R3, and for the aerial part dry matter, the best result obtained when it was obtained in R 5.3, in the absence of the inoculant.
Keywords: nitrogen fertilization; biological fixation; inoculant